GE_GERICHTE P/15417/2007 vom 12. September 2013 - GE Cour de justice (2013)
ABUS DE CONFIANCE; CONTRAINTE(DROIT PÉNAL); TENTATIVE(DROIT PÉNAL); ACTE D'ACCUSATION; MOTIVATION DE LA DÉCISION; TORT MORAL; AVOCAT; HONORAIRES; CONFISCATION(DROIT PÉNAL) ; ALLOCATION AU LÉSÉ | CP.181; CP.138.1; CP.22.1; CP.73.1; CO.49; CPP.81; CPP.9; CPP.433